Quality of life in early-stage Alzheimer's disease: the moderator role of family variables and coping strategies from the patients' perspective - Lima, Sara (2020)
This study assessed the effects of sociodemographic and psychological variables on quality of life (QOL), as well as the moderator role of family variables and coping strategies in the relationship between psychological morbidity and QOL, based on patients’ perspective. Methods: This study used a cross-sectional design. A total of 158 patients with early Alzheimer’s disease completed the Mini-Mental State Examination, the Montreal Cognitive Assessment, the Hospital Anxiety and Depression Scale, the Ways of Coping Questionnaire, the Spiritual and Religious Attitudes in Dealing with Illness, the Family Adaptability and Cohesion Evaluation Scales, the Family Satisfaction Scale, the Family Communication Scale, the Barthel Index, and the Quality of Life in Alzheimer’s Disease Scale. Results: Being a man, having a higher education, and engaging in more exercise activity were associated with better QOL. Lower levels of cognitive impairment, psychological morbidity, and spirituality predicted better QOL. Also, lower levels of functionality, family communication, family satisfaction, and family functioning contributed to worse QOL. Gender, psychological morbidity, and functionality contributed significantly to QOL. Family satisfaction, family communication, and coping strategies moderated the relationship between psychological morbidity and QOL. Conclusion: Intervention in early-stage Alzheimer’s disease should focus on patients’ coping strategies and family context, particularly family satisfaction and communication, to foster QOL.